Characterization of endospore-forming bacteria producing extracellular enzymes isolated from Djurdjura Mountains in Algeria - YAHIAOUI, Merzouk (Algerian Journal of Biosciences, 2021)
Biodiversity in mountains in Algeria appears scanty and has not been thoroughly investigated. However, the mountain soil has been shown as an almost entire reserve of novel enzymes with interesting properties for industrial and environmental applications. In the present study, 30 bacterial strains were isolated from the Djurdjura Mountains in Kabylia (Algeria) and were studied for their ability to produce enzymes to be possibly used in biotechnological processes such as amylase, protease, and chitinase. The characterization of these isolates was carried out using morphological, physiological, and biochemical characteristics. All the data obtained with regards to the phenotypical properties of the isolates, confirmed that the strains belonged to the Bacillus group. In addition, the 16S rRNA gene of the two retained strains KA15 and LK-DZ15 was also amplified and sequenced. Phylogenetic tree was, afterwards, constructed. The nucleotide sequences and blast analyses confirmed that the KA15 and LK-DZ15 strains were closely related to those of the Bacillus altitudinis (accession n°.: MK874318) and Paenibacillus timonensis (accession n°.: MK734103) strains. The presence of amylases, proteases, and chitinases in KA15 and LK-DZ15 isolates are an indicator of their pivotal application in a variety of biotechnological processes.